HOW DO ISLAMIC AND CONVENTIONAL BANK CAPITAL STRUCTURES REACT TO LENDING: DOES POLITICAL TURMOIL MATTER? - Nor Faezah Ghazi Ahmad; Wan Noor Hazlina Wan Jusoh; Muhammad Hamdan Syafieq Ahmad (Journal of Islamic, Social, Economics and Development, 2022)
The pattern of lending growth has changed significantly during the global financialglobal. The deficit of bank lending consequently restricts the consumers and company’s abilityto borrow. The availability of the credit supply in the market can affect the stability of theeconomic growth as the whole. This article is focused on two-fold. First, to examine therelationship between capital structures on bank lending behaviour. Second, to examine theinteraction effect of political turmoil on the relationship between capital structure and banklending behaviour of Islamic and conventional banks. Political turmoil is measured bycorruption (CPI) and election year (ELY) while the capital structure is measured by Tier 1capital and Tier 2 capital. The study employed a panel sample data that consists of 1392 bankyearobservations from 18 dual banking countries from 2006 to 2017. The generalised Methodof Moments (GMM) approach is used to cater to the endogeneity and heterogeneity problem.The results indicate a positive relationship between the capital structure of Islamic banks (IBs)and bank lending behaviour, suggesting that IBs serve the Tier 1 capital as a buffer. Still,conventional banks (CBs) use capital as an incentive device. Furthermore, corruption'sinteraction effect shows that a high level of core capital (Tier 1 capital) can weaken banklending. It is also found that the integrity in the political standpoint in managing corruption torealising stability is vital in ensuring positive credit growth. In conclusion, this study contributesto the proof that corruption can harm the stability of the financial and economic system eventhough the institutions have a huge profit.